2013
DOI: 10.1590/s0104-14282013005000011
|View full text |Cite
|
Sign up to set email alerts
|

Hidrofilicidade de filmes de amido/poli(butileno adipato co-tereftalato) (Pbat) adicionados de tween 80 e óleo de soja

Abstract: Resumo: A incorporação de amido ao polímero poli (butilenoadipatoco-tereftalato) (PBAT) através de blendas com alto teor de amido pode ser uma alternativa para obter embalagens biodegradáveis, minimizar custos e o uso de recursos não renováveis. No entanto, a adição de amido aumenta a permeabilidade ao vapor de água (PVA). A incorporação em filmes com amido de substâncias como óleos vegetais e surfactantes pode diminuir a hidrofilicidade, favorecendo as aplicações destes como embalagens. A hidrofilicidade dos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
(30 reference statements)
1
8
0
1
Order By: Relevance
“…Table 2 shows the thickness values obtained, with the amount of filmogenic solution placed on the plate and thickness. The thickness was determined as the arithmetic average of five random measurements of the area of the film, it was found that with an increase in solids, thickness increased too, same behavior found by Brandelero et al [12] who determined thicknesses of starch films in the same way and obtained a variation in thickness from 0.11 mm to 0.33 mm. On the other hand, Cortez-Vega et al [13] also determined the film thickness of croaker protein isolate by the mean of 10 thickness measurements.…”
Section: Discussionsupporting
confidence: 60%
“…Table 2 shows the thickness values obtained, with the amount of filmogenic solution placed on the plate and thickness. The thickness was determined as the arithmetic average of five random measurements of the area of the film, it was found that with an increase in solids, thickness increased too, same behavior found by Brandelero et al [12] who determined thicknesses of starch films in the same way and obtained a variation in thickness from 0.11 mm to 0.33 mm. On the other hand, Cortez-Vega et al [13] also determined the film thickness of croaker protein isolate by the mean of 10 thickness measurements.…”
Section: Discussionsupporting
confidence: 60%
“…"K" parameter is related to the sorption heat of the multilayer, and when K = 1, it is assumed that there is no interaction of the water vapor in the multilayer or no variation in the energy of sorption in multilayer, which occur in homogeneous solids [39] . In our study, this parameter was not affected by gelatin addition.…”
Section: Moisture Sorption Isothermsmentioning
confidence: 99%
“…The monolayer moisture content (mo) indicates the maximum amount of water that can be adsorbed in a single layer per gram of dry solid and it is a measure of number sorbing sites (MALI et al, 2005). The parameter K is related to the sorption heat of the multilayer, and when k = 1 it assumed that there is no interaction of the water vapor in the multilayer or no variation in the energy of sorption in multilayer, which occur in a homogeneous solids (BRANDELERO et al, 2013). Finally the parameter C is associated with the sorption heat of the monolayer, and the value obtained was lower than reported by Rocha-Selmi et al (2013).…”
Section: Water Sorption Isothermmentioning
confidence: 99%